Manufacturing Consent among Newsworkers at Slovenian Public Radio - Vobič, Igor; Slaček Brlek, Sašo (Javnost-The Public, 2014)
This paper takes an often neglected labour perspective on journalism and investigates labour relations and processes at Slovenian public radio. By taking into account public radio’s specific position in the media environment, which importantly shapes the dynamics between power, property, and work, and by drawing from the work of Michael Burawoy, this paper explores the strategies of manufacturing consent at the Slovenian public radio that minimise potentials of class consciousness among newsworkers and labour-management conflict on one hand and practices and possibilities for resistance and solidarity on the other. Investigation of labour relations and processes at Radio Slovenia was conducted a few months after the Slovenian government adopted austerity measures that have also resulted in layoffs and changes of the employment arrangements of a considerable number of atypical workers at the Slovenian public broadcaster. To gather, assemble, and analyse data, the authors used two research methods: first, participant observation in two newsrooms of Radio Slovenia, and second, in-depth interviews with public radio editors and journalists.